Third Five Year Plan Part I Government of Gujarat 1961 - Planning Commission (Planning Commission, 1961)
The Third Five-Year Plan (1961–66) for Gujarat presents a comprehensive strategy to promote economic growth, social development, and infrastructure enhancement across the state. Key priorities include increasing agricultural productivity through irrigation expansion and improved crop management, strengthening animal husbandry and fisheries sectors, and fostering industrial development, including small-scale and cottage industries. The plan emphasizes the empowerment of local governance through panchayat training and cooperative initiatives, alongside substantial investments in health, education, housing, and labor welfare. Targeted support for backward classes and marginalized communities is integrated to ensure inclusive growth. With financial allocations carefully structured across sectors, the plan seeks to enhance rural livelihoods, improve living standards, and establish a sustainable framework for long-term development in Gujarat.
Government of Gujarat
Government of Gujarat
Keywords: Gujarat; Third Five Year Plan; Agriculture; Irrigation; Animal Husbandry; Fisheries; Industrial Development; Panchayati Raj; Social Welfare; Health Services; Education; Infrastructure